Globalization and Human Rights in the Developing World - Nault, Derrick M.; England, Shawn L.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
Focusing on world regions where human rights abuses are the most serious, extensive and sustained; this book fills a crucial gap in our knowledge of the difficulties and promise of promoting human rights in our global age.
Keywords: Political sociology; Economic policy; International relations; Social justice; Human rights; Political economy; Sociology; Political Sociology; Development Policy; International Relations; Social Justice, Equality and Human Rights; International Political Economy; Sociology, general